A perception study of federalism in the Philippines a study on the barangay officials of Palo, Leyte. - Montes, Lemuel R., Jr.; Brazas-Lim, Ladylyn (Lemuel R. Montes, 2018)
The study attempts to determine the perception of the barangay officials about federalism and what their perception of what will happen to the Philippines if it federalizes. The study interviewed 24 barangay informants from the municipality of Palo, Leyte. Using Public Choice Theory and the Inferential Theory of Political Learning to explain the informant's responses, the common themes included informed responses like state government formation, increased political participation and a different income sharing between levels of government. There were also uninformed and misinformed perceptions like federalism as martial law and the appointment of barangay officials, instead of electing them. Also, when asked about the perceived division of responsibilities in federalism, regardless of the demographics, the informants mostly chose the national as the government unit that would supervise the given responsibilities. This shows the perceived incapacity of the local governments to perform functions that they cannot handle with their current capability. But overall, when the informants were asked if the different levels of government in federalism were capable, most of the informants answered yes to being capable to perform efficiently and effectively in terms of financial capability and human resource. Also, even with the perceived lack of understanding about federalism, the majority of the informants, except the females, said that they supported federalism. And finally, when asked what factors or circumstances could shift their stand regarding federalism, most of them answered that a deeper understanding about federalism can shift their stand, especially from the females who were mostly undecided. To conclude, the majority of barangay officials do not have adequate information about federalism but are positive in the way they perceive what will happen to the Philippines if it federalizes.
A research paper (B.A.S.S. Political Science) -- University of the Philippines, Tacloban.